Mall dan Perilaku Konsumtif Masyarakat Urban - Tuti Alawiyah; Nofal Liata (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
This study aims to explore the consumptive behaviour of people in a modern shopping centre, namely the Mall. Today the Mall is not just a shopping centre or just a place of prestige for some people. Mall at this time has formed a behaviour that reinforces individualism and consumer behaviour without realizing it. This reality is a consequence of an urban society that influenced by capitalist forces in shaping people's behaviour for profit. In this article, the author uses a literature study approach with primary data sources in the form of theoretical literacy related to consumer behaviour and secondary data from electronic media about Mall development. The pattern of consumptive behaviour in the Mall shopping centre which has been considered reasonable keeps the community in the grip of the capitalist. Make society more individualistic and consumptive behaviour.